Construction of two Gateway vectors for gene expression in fungi - Zhu, T.; Wang, W.; Yang, X.; Wang, K.; Cui, Z.
We report the construction of two Gateway fungal expression vectors pCBGW and pGWBF. The pCBGW was generated by introducing an expression cassette, which consists of a Gateway recombinant cassette (attR1-Cmr-ccdB-attR2)under the control of fungal promoter PgpdA and a terminator TtrpC, into the multiple cloning site of fungal vector pCB1004. The pGWBF is a binary vector, which was generated from the plant expression vector pGWB2 by replacing the CaMV35S promoter with PgpdA. The pGWBF can be transformed into fungi efficiently with Agrobacterium-mediated transformation. The applicability of two newly constructed vectors was tested by generating the destination vectors pGWBF-GFP and pCBGW-GFP and examining the expression of GFP gene in Trichoderma viride and Gibberella fujikuroi, respectively. Combining with the advantage of Gateway cloning technology, pCBGW and pGWBF will be useful in fungi for large-scale investigation of gene functions by constructing the interested gene destination/expression vectors in a highthroughput way
Keywords: FUNGAL EXPRESSION VECTOR; GATEWAY CLONING TECHNOLOGY; AGROBACTERIUM-MEDIATED TRANSFORMATION